PEMODELAN EROSI SERTA PREDIKSI ANGKUTAN SEDIMEN DAN HARA PADA SUB DAS BUKIT TINDAWAN DAS KURANJI KOTA PADANG - Junaidi Junaidi; Yuzirwan Rasyid; Andri Ferdinand (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2012)
Land use change from agricultural land into non-agricultural land such as for industries, streets, and others has increased erosion impact, nutrient and sediment in a watershed. That process had caused land degradation in a watershed, therefore, land productivity will decrease and even will cause flood during rainy season and drought during dry season. In order to find out what will happen if land use change takes part, a software using BASIC language was arranged. This software is aimed to simulate erosion process easier. This software uses USLE and Snyder in predicting erosion. Additionally, this software is also able to predict sediment delivery.Keywords : Software conservation, language BASIC.